Návrh zdokonalení marketingového mixu společnosti - Kadlecová, Nikol (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Bakalářská práce se zabývá návrhem na zdokonalení marketingového mixu vzdělávací agentury SOVA STUDIO, která je divizí společnosti SOVA SYSTEMS Č.Ř., spol. s.r.o. V teoretické části jsou přiblíženy základní pojmy marketingu a jeho nástrojů. V analytické části je provedena SWOT analýza společnosti a analýza současného marketingového mixu včetně využití marketingových nástrojů. Na základě zjištěných výsledků je v praktické části vytvořen návrh na zdokonalení marketingového mixu.

The bachelor thesis focuses on proposal for improvement of the marketing mix of education agency SOVA STUDIO, which is division in the company SOVA SYSTEMS Č.R., spol. s.r.o. Theoretical part explains basic concepts of marketing and marketing tools. In the analytical part SWOT analysis is performed on the company and the current situation of marketing mix including the usage of the marketing tools. Based on the results the final part contains propasal for improving the marketing mix.
Proposals for Marketing Mix Elements Improvement
Keywords: marketing; marketingový mix; produkt; cena; propagace; distribuce; SWOT analýza; marketing; marketing mix; product; price; promotion; distribution; SWOT analysis